Meeting the challenge of the plantain (Musa spp.) subsector economic restructuring in cameroon - Tetang, J.T.; Kwa, M.; Temple, L.; Bikoï, A.; Njukwe, E.; Staver, Charles; Ottou, J.F. (2010)
Plantain (Musa spp.) is among the most preferred foods in Cameroon,especially in towns and the forest zones. Almost 40% of production is for homeconsumption. Plantain production is an income generating activity for poor farmers,thus constituting an important component of food security in the country. However,its availability has become a critical issue. An analysis of the sector reveals that,despite the work done so far by the stakeholders to sustain the sector, production(1,315 t in 2004) has remained relatively stagnant since 1975 and production doesn’tmeet demand for consumption. Additionally linkages among, and between, actorsare weak, thus leading to poor learning processes. Fortunately, the policyframework is now strong enough and government commitment is effective since2003 with the launching of a plantain development project and a global program forthe economic restructuring of the plantain sub-sector. To ensure a continuouslearning process, coordinate efforts, strengthen linkages among and between actors,and improve the co-production and diffusion of innovations, it is proposed, amongstothers, to establish a national consultative framework on bananas and plantains.Additionally, the various actors need stimulation and backstopping support fromorganizations having strong experience in the setting up and management ofnetwork and platforms.